Structural and functional characteristics of clustered amylopectin produced by glycogen branching enzymes having different branching properties. (1st May 2020) - Jung, Dahan; Tran, Phuong Lan; Yim, Cheul-Soon; Park, Eun-Ji; Yeom, Su-Jin; Jung, Hee-Gon; Nguyen, Thi Thanh Hanh; Kim, Doman; Park, Jong-Tae
Highlights: Slowly digestible, functional starch was synthesized by a single enzyme treatment. Three clustered amylopectins (CAPs) having distinctive structures were produced. Branch length of CAP significantly impact on the physicochemical properties. Digestibility studies revealed CAP's structural factors other than branch length. Mouse gut-microbiota was affected but differently from in vitro by CAP feeding. Abstract: Three bacterial glycogen branching enzymes (GBEs) having different branching characteristics were used to produce clustered amylopectin (CAP), and structure and functional properties of CAPs were intensively analyzed. Branch distributions of three CAPs varied from very short (DPn = 6.65) to medium (DPn = 14.1). Branch distribution showed profound correlation with hydrodynamic diameter, water solubility, digestibility, and effects on mice gut-microbiota. All the CAPs showed nearly no viscosity and retrogradation. The very short-branch CAP exhibited more than 100-fold water-solubility, 3.5-fold lower α-amylase catalytic efficiency, and 27% lower digestibility in small intestine-mimicking condition than amylopectin. Intriguingly, medium branch CAP had 1.8-fold larger hydrodynamic diameter than the very short one. Mice gut-microbiota composition statistically varied after 12-day feeding of the CAPs, but only the medium chain CAP brought clear positive changes on the gut-microbiota. Consequently, slowly digestible starch was successfully synthesized by the single GBE, but the CAP structure affects in vivo functions in complicated manner.